2023
DOI: 10.1186/s12906-023-04277-1
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical profile and antimicrobial activity of essential oils from two Syzygium species against selected oral pathogens

Sahar S. Salem,
Heba E. Elsayed,
Samah Shabana
et al.

Abstract: Background The genus Syzygium (Myrtaceae) comprises several essential oil-rich species that are utilized traditionally for treating tooth infections and toothache. The current study aimed to extract essential oils (EOs) from the leaves of Syzygium samarangense and Syzygium malaccense cultivated in Egypt for the first time and screen their antimicrobial potential against oral-related pathogens. Methods The intended EOs were extracted using hydrodist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…The antibiotics tested (Tetracycline TC, Gentamicin CN, Streptomycin S, and Amoxicillin AMP) exhibited antibacterial effects against the tested bacteria. Gentamicin was the most effective against all bacteria, while Amoxicillin showed the lowest antibacterial activity (Salem, et al, 2023).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The antibiotics tested (Tetracycline TC, Gentamicin CN, Streptomycin S, and Amoxicillin AMP) exhibited antibacterial effects against the tested bacteria. Gentamicin was the most effective against all bacteria, while Amoxicillin showed the lowest antibacterial activity (Salem, et al, 2023).…”
Section: Discussionmentioning
confidence: 96%
“…Recent reports have indicated that many healthcare-associated, antimicrobialresistant bacteria are not only multidrug-resistant pathogens but also broadly drug-resistant and pandrug-resistant bacteria (Singh & Katoch, 2020). Medicinal plants, known for their therapeutic properties and beneficial pharmacological effects on the human body, are recognized as alternative sources of drugs that could potentially be effective in treating these problematic bacterial infections (Salem et al, 2023, Al-Haj et al, 2019, Boadu & Asase, 2017. a Essential oils, which are volatile terpene hydrocarbons, and their oxygenated derivatives are secondary metabolites, are known for their concentrated natural pharmacologically active ingredients (Boadu & Asase, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These are mainly comprised of low molecular weight compounds, including monoterpenes and phenolic compounds ( Gheorghita et al, 2022 ). Since ancient times, EOs, including clove oil, have been used in oral hygiene as anti-inflammatory and antimicrobial agents ( Saleem et al, 2023 ). The significant antimicrobial activities of EOs are mainly due to their interference with bacterial membranes due to their hydrophobic nature, which affects cellular structures, and their efflux pump, enzymatic inhibition (β-lactamase), and strong antioxidant properties ( Devi et al, 2010 ; Oliveira et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%